A költségek és a költséggazdálkodási tevékenység meghatározó szerepe a vállalat működésében. - Barkovics Ivett (2016)
The knowledge of cost are the basic key element of business operation. I would like to find the answer in my thesis how the knowledge of cost and the role of cost management could influence the company’s operation. Based on my research are proved that the numerical value of the cost are not able to provide enough information about the operation for the management. We need to know the use of the statement of the recovery of the cost and cost management. Ultimately resulting in a comprehensive source of information ont he organization receivesw from the present situations and future activities of the planning decision is a preparatory role.